Expression of Tropomyosin 1 Gene Isoforms in Human Breast Cancer Cell Lines - Syamalima Dube; Santhi Yalamanchili; Joseph Lachant; Lynn Abbott; Patricia Benz; Charles Mitschow; Dipak K. Dube; Bernard J. Poiesz (International Journal of Breast Cancer)
Nine malignant breast epithelial cell lines and 3 normal breast cell lines were examined for stress fiber formation and expression of TPM1 isoform-specific RNAs and proteins. Stress fiber formation was strong (++++) in the normal cell lines and varied among the malignant cell lines (negative to +++). Although TPM1γ and TPM1δ were the dominant transcripts of TPM1, there was no clear evidence for TPM1δ protein expression. Four novel human TPM1 gene RNA isoforms were discovered (λ, μ, ν, and ξ), which were not identified in adult and fetal human cardiac tissues. TPM1λ was the most frequent isoform expressed in the malignant breast cell lines, and it was absent in normal breast epithelial cell lines. By western blotting, we were unable to distinguish between TPM1γ, λ, and ν protein expression, which were the only TPM1 gene protein isoforms potentially expressed. Some malignant cell lines demonstrated increased or decreased expression of these isoforms relative to the normal breast cell lines. Stress fiber formation did not correlate with TPM1γ RNA expression but significantly and inversely correlated with TPM1δ and TPM1λ expression, respectively. The exact differences in expression of these novel isoforms and their functional properties in breast epithelial cells will require further study.